Australian Indigenous higher education: politics, policy and representation - Wilson, Katie; Wilks, J. (Routledge, 2015)
The growth of Aboriginal and Torres Strait Islander participation in Australian higher education from 1959 to the present is notable statistically, but below population parity. Distinct patterns in government policy-making and programme development, inconsistent funding and political influences, together with Indigenous representation during the last 50 years have shaped the higher education participation of Australia’s Indigenous populations. In this article, the authors identify a constant ideological flux between welfare, equity and economic priorities in successive Australian government approaches impacting on equal opportunities for Indigenous Australians in higher education. Maintaining and increasing Aboriginal and Torres Strait Islander participation in higher education requires a continued focus on targets for higher education enrolments, governance and working with Indigenous educators.